Pengaruh Pemasaran Digital Berbasis Syariah terhadap Keputusan Pembelian Produk Halal pada Generasi Z - Ulen Bangun; Fitri Anggriani; Gugun Rahmat Haganta; Gusti Hafiza; Hafizh Nauval; Hesy Al Helani (MAN 4 Kota Pekanbaru, 2026)
This study aims to examine the influence of Sharia digital marketing on halal product purchase decisions among Generation Z in North Binjai District, Binjai City. A quantitative approach with a survey method was employed in this research. Data were collected through questionnaires distributed to 66 Generation Z respondents selected using purposive sampling. The data were analyzed using simple linear regression with the assistance of SPSS software. The findings indicate that Sharia digital marketing has a positive relationship with halal product purchase decisions. The implementation of Sharia principles in digital marketing activities, including honesty, transparency, and ethical promotional practices, enhances consumer trust in selecting halal products. These findings suggest that digital marketing strategies based on Islamic principles can serve as an important factor in encouraging halal product purchasing decisions among Generation Z. This study provides practical implications for halal business actors to optimize digital media utilization while maintaining Islamic business ethics.